Social and economic consequences of HIV and AIDS on children: case study of a high-density community in Harare, Zimbabwe - Joshua Kembo (Taylor & Francis Group, 2010)
We present results from a household-based survey that was conducted in Mabvuku, a high-density community in Zimbabwe. The objective of the study was to improve understanding of social and economic consequences of HIV and AIDS on children. Children affected by HIV and AIDS (CABA) formed the treatment group while those not affected by HIV and AIDS (non-CABA) were the control group. We found that many of the differences in the socio-economic indicators that we studied between CABA and non-CABA were not significant. Therefore our results indicate a gloomy scenario for all the children. These results are consistent with existing literature which indicates that the impact of HIV and AIDS is exacerbated by poverty. Based on evidence from this paper, we conclude that programmes and interventions targeted at children should encompass both CABA and non-CABA within a framework of sustained commitment to improving the lives of these children. We hope that our findings will be used in the formulation of interventions and strategies to improve the situation of children affected by HIV and AIDS and/or living in impoverished communities.